Food policy and economic development in Nigeria - Ojo, M. O. ([Lagos] : Produced for the Central Bank of Nigeria by Page Publishers Services, 1991)
This is a comprehensive treatment of the of the nature of the food problem in a typical developing country. The book further highlights some of the importance of agricultural sector to economic development including largely, as a resource reservoir providing such inputs as labor, raw materials, capital and foreign exchange to the modern industrial sector.
Includes bibliographical references (p. 375-391) and index.
kjo 22/01/2019
Loans
Keywords: Food supply; Nutrition policy; Agriculture and state; Nigeria